2021
DOI: 10.1101/2021.02.25.432762
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The type 2 asthma mediator IL-13 inhibits SARS-CoV-2 infection of bronchial epithelium

Abstract: Rationale: Asthma is associated with chronic changes in the airway epithelium, a key target of SARS-CoV-2. Many epithelial changes are driven by the type 2 cytokine IL-13, but the effects of IL-13 on SARS-CoV-2 infection are unknown. Objectives: We sought to discover how IL-13 and other cytokines affect expression of genes encoding SARS-CoV-2-associated host proteins in human bronchial epithelial cells (HBECs) and determine whether IL-13 stimulation alters susceptibility to SARS-CoV-2 infection. Methods: We u… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…SARS-CoV-2-specific CD4 + effector cells generally do not express Th2 traits ( 39 ), which could play a protective role as shown by the lower susceptibility and less severe outcomes of COVID-19 in asthmatic and atopic patients ( 40 , 41 ). Accordingly, IL-13 was shown to reduce viral burden, possibly by downregulating the expression of angiotensin-converting enzyme 2 (ACE2) in airway epithelial cells ( 42 , 43 ). In addition, M2 macrophage polarization induced by IL-4 and IL-13 fostered tissue repair and resolution of inflammation in ARDS ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…SARS-CoV-2-specific CD4 + effector cells generally do not express Th2 traits ( 39 ), which could play a protective role as shown by the lower susceptibility and less severe outcomes of COVID-19 in asthmatic and atopic patients ( 40 , 41 ). Accordingly, IL-13 was shown to reduce viral burden, possibly by downregulating the expression of angiotensin-converting enzyme 2 (ACE2) in airway epithelial cells ( 42 , 43 ). In addition, M2 macrophage polarization induced by IL-4 and IL-13 fostered tissue repair and resolution of inflammation in ARDS ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…It all suggests that IL-13 released from T helper 2 (Th2) and type 2 innate lymphoid cells (ILC2) cells at the mucosal sites during type 2 inflammation in allergic asthma on top of other known morphological and transcriptional changes might potently induce ACE2 deglycosylation and redistribution which might alter SARS-CoV-2 infection efficiency. Recent publications show that IL-13 can inhibit SARS-CoV-2 infection, as well as can reduce intracellular viral load and cell-to-cell transmission in airway epithelial cells 14, 38 . IL-13 induced mucus hyperproduction can inhibit SARS-CoV-2 infection by forming a physical barrier, but even after mucus removal, viral loads remained to be lower upon IL-13, suggesting further mechanisms to be involved 14 .…”
Section: Resultsmentioning
confidence: 99%
“…Jackson et al evaluated expression of ACE2 in the airways of in adults and children with asthma and found that ACE2 expression was lower in the airway of patients with allergic sensitization and asthma compared with patients with nonallergic asthma [29]. Reduced ACE2 expression combined with expression of immunomodulators could contribute to lower COVID-19 susceptibility for patients with nonallergic asthma, and this hypothesis is supported by a growing body of preclinical and clinical evidence [29,[32][33][34][35][36][37]. This study had a number of strengths, including a large sample size of patients from across the United States.…”
Section: Discussionmentioning
confidence: 99%